The effect of hotel and restaurant tax revenue on the original income of the blitar City Area - Nosilia Fristiani; Yesinta Margareta (Indonesia Accounting Research Journal, 2025)
This study aims to determine the Influence of Hotel Tax and Restaurant Tax on Original Income of Blitar City. The sample of this study uses annual data on Regional Taxes and Regional Original Revenues. The number of samples used is 5 years from 2020-2024. The hypothesis test in this study used multiple linear regression analysis with SPSS. The results of the research on hotel taxes and restaurant taxes have an effect but are not significant on the Original Revenue of the Blitar City Area. The results of the study show that the influence of hotel tax revenue and restaurant tax is quite strong.